The little gulay book - Gonzalez, Gene (Pasig City, 2004)
The book emphasizes the nutritional value and cultural significance of indigenous vegetables, encouraging their inclusion in everyday meals. It also aims to revive traditional Filipino cooking practices while inspiring creativity in using local produce.
Keywords: Vegetarian cooking